2022
DOI: 10.3390/gels8080510
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Treatment and Hydrogel: Current Insights and State of the Art

Abstract: Aqueous gels formulated using hydrophilic polymers (hydrogels) and those based on stimuli-responsive polymers (in situ gelling or gel-forming systems) attract increasing interest in the treatment of several eye diseases. Their chemical structure enables them to incorporate various ophthalmic medications, achieving their optimal therapeutic doses and providing more clinically relevant time courses (weeks or months as opposed to hours and days), which will inevitably reduce dose frequency, thereby improving pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 176 publications
0
9
0
Order By: Relevance
“…According to Malik et al, GDD implantation is associated with 5-year success rates of over 70% in primary childhood glaucoma, and trabeculectomy remains an effective procedure in compliant patients in whom multiple postoperative examinations under anesthesia are possible [22]. Aqueous gels formulated using hydrophilic polymers (hydrogels) and those based on stimuli-responsive polymers (in situ gelling or gel-forming systems) have attracted increasing interest in the treatment of several eye diseases [23]. Improved drug delivery systems may inhibit fibroblast proliferation and yield better surgical outcomes in TLE with mitomycin and GDD implantation.…”
Section: Discussionmentioning
confidence: 99%
“…According to Malik et al, GDD implantation is associated with 5-year success rates of over 70% in primary childhood glaucoma, and trabeculectomy remains an effective procedure in compliant patients in whom multiple postoperative examinations under anesthesia are possible [22]. Aqueous gels formulated using hydrophilic polymers (hydrogels) and those based on stimuli-responsive polymers (in situ gelling or gel-forming systems) have attracted increasing interest in the treatment of several eye diseases [23]. Improved drug delivery systems may inhibit fibroblast proliferation and yield better surgical outcomes in TLE with mitomycin and GDD implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma is a neuropathy characterized by loss of the visual field and blindness caused by the destruction of ganglion cells [228,229]. While clinical trials have shown promising results in reducing intraocular pressure, existing non-hydrogel methods entail adverse effects such as ocular inflammation, itching, or visual disturbances from topical treatments [228,230,231]. Smart chitosan-based formulations have emerged as a potential solution for glaucoma since they are known for their biocompatibility and ability to absorb water [232].…”
Section: Drug Delivery In the Treatment Of Non-cancer Diseasesmentioning
confidence: 99%
“…These current treatments aim to lower or control IOP. Popular drugs include β-blockers, α-agonists, carbonic anhydrase inhibitors, prostaglandin analogs, and cholinergic drugs [ 98 ], though their bioavailability is limited. The main obstacles to treating glaucoma are patient compliance and drug efficacy, which are being further questioned by frequent daily dosing [ 99 , 100 , 101 ].…”
Section: Advances In Nanogels For Ocular Diseasesmentioning
confidence: 99%